Clinical phenotypic and genotypic characterization of NPRL3-related epilepsy - Zhang, Hongwei; Deng, Jie; Wang, Xiaohui; Chen, Chunhong; Chen, Shuhua; Dai, Lifang; Fang, Fang (Frontiers in Neurology, 2023)
Background As one of the assembly factors of the GATOR1 protein complex in the mechanism of rapamycin pathway, NPRL3 plays an important role in the pathogenesis of epilepsy. However, the correlation between genotype and clinical phenotype in patients with NPRL3-related epilepsy has not been clarified. Methods A total of 11 Chinese children with NPRL3-related epilepsy were identified through whole-exome sequencing (WES). The data from the clinical presentation, laboratory data, brain imaging findings, genetic results, and treatment methods were collected. All previously reported cases with NPRL3-related epilepsy were collected and reviewed through PubMed search. Results Among the 11 children, eight have not been reported, and two of them presented infantile spasms (ISs) as a new phenotype of NPRL3-related epilepsy. In addition, WES identified five frameshift mutations, three nonsense mutations, two missense mutations, and one exon deletion. Based on bioinformatics analysis, it was found that two missense mutation sites were highly conserved, and the c.400G>A mutation site of the NPRL3 gene caused the alteration of the protein structure. To date, 88 patients have been reported with NPRL3-related defects, including our 11 cases. The most common presentations were sleep-related hypermotor epilepsy (SHE), frontal lobe epilepsy (FLE), and temporal lobe epilepsy. A majority of patients (70%) presented normal neuroimaging results, and focal cortical dysplasia was the most common neuroimaging abnormality (62.5%). Among the NPRL3 gene mutations, loss of function (nonsense mutations, frameshift mutations, and exons deletion) was the most common genetic variation (75%). For 73% of patients with NPRL3-related epilepsy, monotherapy of sodium channel blockers was effective. Surgery was effective for 75% of children with neuroimaging abnormalities. Two cases unresponsive to surgery or anti-seizure medications were treated with ketogenic diets (KD), which were effective. One case was treated with rapamycin at an early stage of epilepsy, which was effective as well. Conclusion NPRL3-related epilepsy has high clinical and genetic heterogeneity. SHE and FLE are the most common clinical presentations. Furthermore, ISs are the new phenotypes of NPRL3-related epilepsy, while the variants c.275G>A, c.745G>A, and c.1270C>T may be the most common NPRL3 gene mutations. Sodium channel blockers, surgery, KD, and rapamycin may be the potential treatments for these patients. Our study expanded the clinical and genetic spectrum of NPRL3-related epilepsy and provided important information for the precise treatment of patients.